Youth unemployment in selected Persian Gulf countries : a comparative analysis of Saudi Arabia, the UAE, and Oman - Merenics, Viktoria; Abdallah, Kareem Issam; Mammadov, Orkhan; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This bachelor thesis explores the issue of youth unemployment in the Gulf Cooperation Council (GCC) countries, focusing specifically on Saudi Arabia, the United Arab Emirates, and Oman. The aim is to identify and compare key economic, demographic, social, and educational factors influencing the integration of young people into the labour market. The theoretical part presents the main drivers of youth unemployment, including rapid population growth, gender disparities, cultural expectations, and mismatches between educational outcomes and labour market needs. The practical part includes a comparative analysis using indicators such as GDP per capita, unemployment by age, gender, and education level. The findings reveal significant differences among the three countries, with the UAE showing more stability, while Saudi Arabia and Oman face structural challenges, particularly regarding female and graduate youth employment. The study concludes that addressing youth unemployment in the GCC requires not only economic reforms but also comprehensive changes in education, gender policy, and employment strategies tailored to young people’s needs.
Vedoucí práce: Kareem Issam Abdallah
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses